In Vitro Antileishmanial Effects of Saffron Compounds, Crocin and Stigmasterol, on Iranian Strain of Leishmania major (MHOM/IR/75/ER) - Reza RANJBAR; Peyman SHAYANFAR; Mahmood MANIATI (Iranian Journal of Parasitology, 2021)
Background: Due to numerous side effects of common drugs in treatment of leishmaniasis, new therapeutic approaches focus on herbal compounds. Therefore, we aimed to determine the effect of crocin and stigmasterol on in-vitro growth of promastigotes and amastigotes of Leishmania major in the Department of Parasitology, Pasteur Institute, Tehran, Iran in 2018.